2017
DOI: 10.1186/s12954-017-0159-9
|View full text |Cite
|
Sign up to set email alerts
|

Social-structural factors influencing periods of injection cessation among marginalized youth who inject drugs in Vancouver, Canada: an ethno-epidemiological study

Abstract: BackgroundInjection drug use is associated with HIV and hepatitis C transmission, overdose, and other preventable harms. These harms are heightened for structurally vulnerable injection drug-using populations, as their social conditions pose barriers to safer injecting. Previous research on injection cessation has largely focused on adult drug-using populations. Little qualitative work has examined the social, structural, and environmental factors that shape periods of injection cessation among youth and young… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 79 publications
2
35
0
Order By: Relevance
“…During marginalization, there is an increase in both the perceived and objective distance to resources such that there is differential access to, and inequity in education, employment, housing and affordable health care services (see Figure ). For instance, an ethno‐epidemiologic study that examined social, structural, and environmental factors that influence periods of injection cessation among marginalized youth who inject drugs in Vancouver, Canada, found that access to harm reduction youth‐focused services, provision of housing, and social support were important factors that influenced injection cessation (Boyd et al., ). A participant in this study reported his residential location in Vancouver's inner‐city drug scene limited his ability to escape the drug scene.…”
Section: The Link Between Social Determinants Of Health and Marginalimentioning
confidence: 99%
“…During marginalization, there is an increase in both the perceived and objective distance to resources such that there is differential access to, and inequity in education, employment, housing and affordable health care services (see Figure ). For instance, an ethno‐epidemiologic study that examined social, structural, and environmental factors that influence periods of injection cessation among marginalized youth who inject drugs in Vancouver, Canada, found that access to harm reduction youth‐focused services, provision of housing, and social support were important factors that influenced injection cessation (Boyd et al., ). A participant in this study reported his residential location in Vancouver's inner‐city drug scene limited his ability to escape the drug scene.…”
Section: The Link Between Social Determinants Of Health and Marginalimentioning
confidence: 99%
“…They included lower socioeconomic status, lack of social support, discrimination and insufficient methadone doses [ 26 30 ]. Meanwhile, some structural barriers were also recognized to predict non-adherence to MMT including patients’ satisfaction with healthcare services, poverty, jobs and housing, in both developed and developing countries [ 19 , 23 , 24 , 28 , 31 33 ]. However, these factors varied across study settings, and very few ones have focused on the provision of MMT in relation to other HIV services.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the central role PWID occupy in the HCV epidemic, few are offered DAA treatment because of concerns regarding suboptimal adherence, cost, and medication resistance (12,13). People who inject drugs face many adherence challenges, including mental illness, homelessness, lack of positive social support, poor adherence-related skills, low HCVrelated knowledge, and poor access to and mistrust of the health care system (14)(15)(16)(17). Yet, most PWID with HCV are willing to undergo treatment (18)(19)(20)(21), and the simplicity of DAA therapy promises great advantages for achieving HCV cure.…”
mentioning
confidence: 99%